A Putative Plasmodium RNA-Binding Protein Plays a Critical Role in Female Gamete Fertility and Parasite Transmission to the Mosquito Vector - Kumar, Sudhir; Abatiyow, Biley A.; Haile, Meseret T.; Oualim, Kenza M. Z.; Leeb, Amanda S.; Vaughan, Ashley M.; Kappe, Stefan H.I. (Frontiers in Cell and Developmental Biology, 2022)
Plasmodium falciparum sexual stages called gametocytes are critical for parasite transmission from the human host to the mosquito host. Mature gametocytes generate fertile gametes upon activation inside the mosquito midgut. While a number of parasite genes have been described that are critical for gametogenesis and fertility, no parasite gene was shown yet to have a unique function in female (macro) gametes of P. falciparum. The genome of P. falciparum encodes numerous RNA-binding proteins. We identified a novel putative RNA-binding domain protein, which we named Macrogamete-Contributed Factor Essential for Transmission (MaCFET), that is expressed in the asexual and sexual stages. Pf macfet¯ parasites that carry a deletion of MaCFET develop normally as asexual stages, indicating that PfMaCFET function is not essential for the asexual proliferation of the parasite in vitro. Furthermore, Pf macfet¯ male and female gametocytes develop normally and undergo activation to release microgametes and macrogametes. However, by utilizing genetic crosses we demonstrate that Pf macfet¯ parasites suffer a complete female-specific defect in successful fertilization. Therefore, Pf MaCFET is a critical female-contributed factor for transmission to the mosquito. Based on its putative RNA-binding properties, PfMaCFET might be in involved in the regulation of mRNAs that encode female-specific functions during fertilization or post fertilization.